Research on the contributions of modern buildings to urban aesthetics / Ida Noorjulianti bt. Haji Sugijanto - Ida Noorjulianti, Haji Sugijanto (1988)
Generally, we take for granted that the progress and increase of human intelligence, ability, and goals are for the good of all mankind, nature, and the universe, to achieve a better living environment. Is this so? Just look around you, at the world and we will find the answer For if we observe, as time passes, many events and changes have taken place. Some of these events left a 'beautiful memory to ponder and take note of and yet some of it is like 'criminals, robbing us of the natural gifts presented by God in each of us, man and nature.